Is radical innovation in architecture crucial to sustainability? Lessons from three Scottish contemporary buildings. (4th July 2018) - Nigra, Marianna; Dimitrijevic, Branka
ABSTRACT: Radical innovation is largely recognised as a medium for advancement, a source of growth for economies and a trigger for progress in different economic sectors. Often, this type of innovation is identified with technological advancements, disruptive phenomena and the creation of new systems and dynamics. Yet, within the context of a changing world, in which principles of economic, environmental and social sustainability are largely adopted as common objectives, a reflection on the type of progress and the need for radical innovation is necessary with the aim of informing on their impacts and effectiveness. This work presents an analysis of a number of contemporary Scottish architectural designs, developed under the aegis of sustainability principles, and explores the types of sustainable innovations introduced and the results achieved by analysing the type of design change that triggered specific sustainable results, demonstrating alternative innovation strategies, other than the radical one. This analysis provides a basis for discussion on the need for radical innovation in the context of sustainable architecture and explores the role of other types of innovation against the results achieved. This discussion could contribute to a better understanding of the current state of practice in architectural design, as well as in policy-making in regard to the design and management of the future built environment.